Mitigating The Spread of Radical Ideas Through Counter-Radicalization Based on Local Wisdom - Samsul Arifin; Hariri, Achmad; Prakasa, Satria Unggul Wicaksana; Asis, Asis; Hakim, Lukman (Audito Comparative Law Journal (ACLJ), 2024)
Understanding efforts made by the government to counter radicals are limited to three (3) major patterns: national preparedness, deradicalization, and counter-radicalization. However, these efforts have yet to be effective enough. The facts show that more than efforts to fight the spread of radicalism are needed with law enforcement. On the one hand, we can see in some areas, especially those in Pamekasan district, that local wisdom also significantly influences efforts to counteract radicalism. The unwritten rules of living in society have indirectly fortified themselves from radical ideas. On this basis, the problems that will be raised in this study are related to the local wisdom of the Pamekasan Madura community, which is considered capable of resisting the entry of radical ideas; the purpose of this study is to find out that the norms that live in the community have succeeded in counteracting.